Prevalence of metabolic syndrome and its' components in the young adult-students of universities in Lodz, Poland - Małgorzata Koziarska-Rościszewska; Maryla Panasiuk; Katarzyna Cypryk (Pediatric Endocrinology, Diabetes and Metabolism)
Introduction and aim of the study: Early identification of people at cardiovascular diseases (CVD) risk is crucial for the effective management. The aim of the study was to assess the prevalence of metabolic syndrome (MS) and its? components in young adults. Material and methods: The study (2006-2007) was conducted on the group of 1019 students: 709 women (W), 310 men (M), aged 18-38 years (mean 24.6) attending a primary care practice. A clinical interview was provided and anthropometric measurements and laboratory investigation were done. Body mass index (BMI), waist-hip ratio (WHR) and insulin-resistance (IR) were calculated. Results: Mean BMI was 24.4 kg/m2 in men and 21,29 kg/m2 in women. Overweight (BMI=25-30 kg/m2) was diagnosed in 17.66% and obesity (BMI>30 kg/ m2) in 3.02% of the study population. The prevalence of hypertension (HA) according to ATPIII/IDF (BP ?130/85 mmHg) was revealed in 4.61%; acc. WHO (BP ?140/90 mmHg) in 2.06%. There were no women with HA in the examined population. Fasting plasma glucose >100 mg/dL occurred in 0.78%. Hypercholesterolaemia was found in 12.56%; high levels of LDL and TG in 2.06% and 7.69% respectively and low HDL level in 6.64%. Metabolic syndrome acc. WHO criteria was diagnosed in 2.65%; acc. ATP III in 0.59% and acc. IDF in 0.98% of the study population. All MS components, except hyperglycaemia, occurred statistically more frequently in men than in women (p <0.05). Conclusions: Our study shows a relatively high incidence of overweight, obesity and lipid disturbances, whereas other CVD risk factors are of a relatively lower percentage in young adults in Poland. The results confirm the higher incidence of MS and its components in men than in women. Revealing individuals at risk on the earliest stages allows to cope with the incorrect metabolic processes and, as a result, optimizing prevention activities based on primary care practice. Obesity is the greatest challenge for the public health.